Pengaruh Penanaman Modal Dalam Negeri (PMDN) terhadap Pertumbuhan Ekonomi Provinsi Lampung - Suradi (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2023)
Economic growth cannot be separated from the factors that support it, one of which is investment. Currently, investment has become a very strong instrument in encouraging regional economic growth, including Lampung Province. One source of investment is Domestic Investment. The aim of this research is to analyze the influence of Domestic Investment on the economic growth of Lampung Province. The research method used is the analytical statistical method. This method is used to see the influence of Domestic Investment on the economic growth of Lampung Province. The analysis technique uses simple linear regression. The research results showed that Domestic Investment had no effect on the economic growth of Lampung Province. Keywords: domestic investment, economic growth